2009
DOI: 10.1007/s11899-009-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of c-Kit mutations in acute myelogenous leukemia

Abstract: c-Kit is a receptor tyrosine kinase (RTK) with a pivotal role in melanogenesis, gametogenesis, and hematopoiesis. Aberrantly activated RTK and related downstream signaling partners were identified as key elements in the molecular pathogenesis of several malignancies. This finding culminated in a two-class model integrating constitutive activating and maturation arrest-inducing mutations as key elements for the pathogenesis of acute myelogenous leukemia (AML). c-Kit is expressed by myeloblasts in about 60% to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 52 publications
2
64
0
1
Order By: Relevance
“…We reported that Axl is necessary for maintaining activation of c-Kit, 20 which belongs to the same type III RTK family as FLT3. 31 Indeed, FLT3 inhibitors used in clinical trials have also been shown to inhibit c-Kit activity. 18 We thus hypothesized that FLT3 could be a potential target of Axl, at least in cases of FLT3- with Axl-Fc, the physical interaction between Axl and FLT3 was disrupted ( Figure 3C), suggesting not only that Axl is a positive regulator of FLT3 phosphorylation but also that this regulation likely occurs through physical interaction between activated Axl and FLT3.…”
Section: Resultsmentioning
confidence: 99%
“…We reported that Axl is necessary for maintaining activation of c-Kit, 20 which belongs to the same type III RTK family as FLT3. 31 Indeed, FLT3 inhibitors used in clinical trials have also been shown to inhibit c-Kit activity. 18 We thus hypothesized that FLT3 could be a potential target of Axl, at least in cases of FLT3- with Axl-Fc, the physical interaction between Axl and FLT3 was disrupted ( Figure 3C), suggesting not only that Axl is a positive regulator of FLT3 phosphorylation but also that this regulation likely occurs through physical interaction between activated Axl and FLT3.…”
Section: Resultsmentioning
confidence: 99%
“…25 Implication of the D816V mutation in the pathogenesis of myeloproliferative disease demonstrates a critical role of KIT D816V transduced signals in the development of myeloid cells. 26,27 Although extrapolations regarding the physiological mechanisms of Kit signaling during myeloid cell differentiation must be made with caution, it is thus reasonable that similar signaling events are activated by the mutant KIT D816V receptor and valuable insights can be provided by such a model. We therefore generated a conditional mouse line with knock-in of a chimeric KIT receptor carrying the D816V mutation in the ROSA26 locus.…”
Section: Resultsmentioning
confidence: 99%
“…Other kinase activating mutations have been found in the oncogene c-KIT in gastrointestinal stromal tumors (GIST), acral or mucosal melanoma, endometrial carcinoma, germ cell tumors, myeloproliferative diseases, and leukemias, which is the mutations cause constitutive activation of c-KIT (Malaise, Steinbach et al 2009). c-KIT is a transmembrane cytokine receptor tyrosine kinase that is expressed on the surface of hematopoietic stem cells.…”
Section: Activating Mutations At C-kitmentioning
confidence: 99%